Pola Konsumsi Bahan Makanan Sumber Natrium pada Pasien Hipertensi Rawat Jalan di Rumah Sakit Tugurejo Semarang - Nur Yunaida Fauziah; Sufiati Bintanah; Erma Handarsari (Universitas Muhammadiyah Semarang, 2013)
Hypertension is a risk factor for cardiovascular disease that often occurs without symptoms. In general, people do not know that he was suffering from hypertension. New symptoms arise after a complication occurs in organs such as kidneys, eyes, brain, heart. Because it does not cause symptoms, hypertension is also known as the silent killer or killers in disguise (Hans Pwolf,1994). High blood pressure is also influenced by behavioral factors ie poor diet such as sodium consuming more resources, especially the excessive salt causes the sodium in the liquid increases. Increasing the volume of fluid causes increased blood volume rises, so the impact on the incidence of hypertension. (Smith, 1988). The results of the household health survey in 1995 showed the prevalence of hypertensive disease in Indonesia is quite high at 83 per 1000 member households ranged from 1.8 to 28.6%. (Hull Alllison, 2001)The prevalence of hypertension in Tugurejo Hospital in January-December 2010 wasranked one of the top 10 diseases, with a number of 6504 patients.This study aims to find out about the consumption patterns of food sources of sodium in hypertensive patients in a hospital outpatient tugurejo Semarang. The samples obtained are 40 samples which are all eligible: Age of patients ranged 33-80 years, berdominisili in Semarang and the patient can take berkomunikasi.Jenis data collected is of primary and secondary data. Primary data include sodium consumption data by semi-quantitative food frequency and eating habits. Secondary data includes the data base name, age, sex, blood pressure taken from medical records. The results of the study were mostly (62.5%) samples were aged 45-60 years, most of the sexes (67.5%) samples were women 27 people, mostly the kind of work (45.0%) samples were housewives 18 people . Most of the samples with Na intake (2000-4000 mg) as many as32 people, and hypertension category were as many as 27 people. Most (65.0%) samples in systolic blood pressure (category average) as many as 26 people, majority (77.5%) samples in diastolic blood pressure (category average) as many as 31 people. Most of the samples stilluse MSG flavor enhancer, salt, and tofu, the frequency of consumption of sodium sources most 1-3 times per day.Keyword : hypertension, natrium intake, cardiovascular diseases